Federalism in Asia - He, Baogang 1957-; Galligan, Brian 1945-; Inoguchi, Takashi (Edward Elgar, 2007)
Until now there have been few attempts to examine the different models of federalism appropriate in Asia, let alone to trace the extent to which these different perspectives are compatible, converging, or mutually influencing each other. This book redresses the balance by demonstrating the varieties of Asian federalism.